2003
DOI: 10.1111/j.1469-8749.2003.tb00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of drooling in children with cerebral palsy attending special schools

Abstract: Prevalence of drooling in children with cerebral palsy (CP) and its severity across dental age (i.e. children with primary, mixed, and permanent dentitions) was investigated. One hundred and sixty children and adolescents (91 males, 69 females; mean age 10 years 10 months, SD 4 years 2 months; range 4 to 18 years) with CP who attended special schools were involved in this study. Sixty eight per cent of participants had spastic CP with the majority (45%) diagnosed as having quadriplegia. Presence or absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 22 publications
6
47
1
2
Order By: Relevance
“…Parents of 1437 children with CP reported that 34% sometimes found drooling to be a problem, while 16% responded that it was often a problem [1]. This percentage was even higher among CP children attending special schools: 58% (93 of 160) children, aged 4-18 years, drooled; 33% (53/160), drooled severely [12].…”
Section: Introductionmentioning
confidence: 84%
“…Parents of 1437 children with CP reported that 34% sometimes found drooling to be a problem, while 16% responded that it was often a problem [1]. This percentage was even higher among CP children attending special schools: 58% (93 of 160) children, aged 4-18 years, drooled; 33% (53/160), drooled severely [12].…”
Section: Introductionmentioning
confidence: 84%
“…2 Chronic aspiration may be further complicated by the presence of gastroesophageal reflux disease (GERD) and drooling, which are present in more than 50% of cases. 32,33 Drooling is secondary to impaired volitional movements whereas posterior salivation causes recurrent aspiration and subsequent pulmonary infections. 34 Other common static conditions include Arnold-Chiari and central arteriovenous malformations, which may be present with only subtle clinical evidence of OPD.…”
Section: Neurologic Disordersmentioning
confidence: 99%
“…Tahmassebi and Curzon [3] report that 58% of children with CP suffer from drooling, of which 33% have severe drooling. Crysdale [4] estimates that 10-15% of children with CP have significant drooling.…”
Section: Prevalence Of Droolingmentioning
confidence: 99%